2007
DOI: 10.1038/sj.mp.4001941
|View full text |Cite
|
Sign up to set email alerts
|

Val66met polymorphism and serum brain-derived neurotrophic factor levels in bipolar disorder

Abstract: group to cytosine residues in the dinucleotide sequence CpG. 1 A lack of alimentary methyl-group donors, like folate, owing to starvation, may be the underlying cause of both elevated homocysteine and DNA hypomethylation in AN.To further investigate possible epigenetic contributions to the pathophysiology of eating disorders, we analyzed the expression and promoter-specific DNA methylation of two genes, SNCA and HERP, recently described to be altered in alcohol dependence. 5,7 We found a decreased SNCA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 9 publications
6
26
0
Order By: Relevance
“…However, in a recent study we showed that met carriers did not present lower levels of BDNF in their sera. 7 Thus, BD patients who are met-carriers seem to be more likely to present cognitive impairment and rapid cycling; however, such findings were not correlated with lower BDNF serum levels.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, in a recent study we showed that met carriers did not present lower levels of BDNF in their sera. 7 Thus, BD patients who are met-carriers seem to be more likely to present cognitive impairment and rapid cycling; however, such findings were not correlated with lower BDNF serum levels.…”
Section: Introductionmentioning
confidence: 73%
“…12 Even though some studies have suggested an association of the val66met polymorphism and BDNF expression, negative reports on this association have been described. 7,22 In any case, genetic influences on cognition might be subtler, and involve synergic polymorphism interaction, such as the one recently demonstrated in the general population between the RE1-silencing transcription factor (REST) gene and the BDNF val66met polymorphism. 23 Our study has other limitations that must be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Excluded: no MDD phenotype, 8,14,67,68,[85][86][87][88][89][90][91][92][93][94][95][96][97] no case-control design, 22,31,[98][99][100][101][102][103] no adults 104,105 and no Hardy-Weinberg equilibrium (HWE). 106 Included: Caucasian studies, 11,[33][34][35][36][37][38][39][40] Asian studies 19,21,[41][42][43] and gender studies.…”
Section: Meta-regression Analysesmentioning
confidence: 99%
“…Genomic DNA was extracted using standard procedures (27). The genotyping of the BDNF Val66Met polymorphism was performed using a 5' nuclease TaqMan allelic discrimination assay on the Applied Biosystems 7500 Real-Time PCR Systems (Applied Biosystems, Carlsbad, CA, USA).…”
Section: Blood and Genetic Analysismentioning
confidence: 99%